Water, land, and air: how do residents of Brazilian remote rural territories travel to access health services? - Patty Fidelis de Almeida; Adriano Maia dos Santos; Lucas Manoel da Silva Cabral; Eduarda Ferreira dos Anjos; Márcia Cristina Rodrigues Fausto; Aylene Bousquat (BMC, 2022)
Abstract Background Ensuring adequate and safe means of travel is essential for maintaining and improving the health and well-being of residents of rural communities worldwide. This article maps costs, distances, travel times, and means of elective and urgent/emergency health transport in Brazilian remote rural municipalities. Methods Multiple case studies were conducted in 27 remote rural municipalities using a qualitative method. A total of 178 key informants (managers, doctors, and nurses) were interviewed. Secondary data from national information systems were analyzed for the socioeconomic characterization, to identify the costs, distances, and travel times. Through the thematic content analysis of the interviews, the means of transport, and strategies developed by managers, professionals and users for their provision were identified. Results The costs of traveling between remote rural municipalities and locations where most of specialized and hospital services are centered can compromise a significant part of the families' income. The insufficiency, restriction of days, times, and routes of health transport affects the selection of beneficiaries based on socioeconomic criteria in places of high vulnerability and less investment in road infrastructure. In remote rural municipalities, travelling to seek health care involves inter-municipal and intra-municipal flows, as their territories have dispersed populations. Several means of transport were identified - air, river, and land - which are often used in a complementary way in the same route. Some patients travel for more than 1000 km, with travel times exceeding 20 h, especially in the Amazon region. While the demands for urgent and emergency transport are partially met by national public policy, the same is not true for the elective transport of patients. The impossibility of providing health transport under the exclusive responsibility of the municipalities is identified. Conclusions For the remote rural municipalities populations, the absence of national public policies for sufficient, continuous, and timely provision of transport for health services worsens the cycle of inequities and compromises the assumption of the universal right to health care.